Drug resistant variants of hepatitis C virus genotype 1b in Russia: analysis of aminoacid substitutions in NS5a and core proteins - V. S. Kichatova; A. A. Karlsen; O. V. Isaeva; S. A. Solonin; E. Yu. Malinnikova; K. K. Kyuregyan; M. I. Mikhailov (Журнал инфектологии)
Aim. To determine the prevalence of amino acid substitutions in hepatitis C virus NS5a and core proteins which are associated with resistance to direct-acting antivirals and interferon in genotype 1b (HCV-1b) strains circulating in Russia. Materials and methods. Nucleotide sequences of NS5a (n=93) and core (n=30) of HCV-1b were obtained using direct sequencing of respective amplified genome fragments. The search for resistance associated substitutions was performed for amino acid positions 28, 29, 30, 31, 32, 58, 62, 92, 93 of NS5a, and 70 and 91 amino acid positions of core proteins, respectively. Results. The total proportion of HCV-1b strains carrying resistance associated substitutions in NS5a was 22,6% (21/93). The total detection rate of L31M and Y93H substitutions that are associated with resistance to the majority of NS5a inhibitors was 10,8%. Less clinically significant substitutions L28M, R30Q, P58S/T, A92T were detected too. The proportion of infections caused by HCV-1b strains that are potentially resistant both to interferon and NS5a inhibitors was 10% (10/30). Conclusion. Testing of HCV-1b infected patients for background resistance profile could be a useful tool to prevent the choosing of initially ineffective treatment regimen.